2007
DOI: 10.1016/j.jcrs.2007.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Canaloplasty: Circumferential viscodilation and tensioning of Schlemm's canal using a flexible microcatheter for the treatment of open-angle glaucoma in adults

Abstract: Circumferential viscodilation and tensioning of Schlemm's canal was a safe and effective surgical procedure to reduce IOP in adult patients with OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(189 citation statements)
references
References 30 publications
10
167
3
9
Order By: Relevance
“…In line with our results, Ayyala et al (2011) observed a more pronounced IOP reduction after 12 months with fewer medications in trabeculectomy (mean 43%) than canaloplasty (mean 32%). Canaloplasty had a better IOP reduction when performed in combination with cataract surgery (Lewis et al 2007(Lewis et al , 2011Shingleton et al 2008;Bull et al 2011;Arthur et al 2013;Tetz et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our results, Ayyala et al (2011) observed a more pronounced IOP reduction after 12 months with fewer medications in trabeculectomy (mean 43%) than canaloplasty (mean 32%). Canaloplasty had a better IOP reduction when performed in combination with cataract surgery (Lewis et al 2007(Lewis et al , 2011Shingleton et al 2008;Bull et al 2011;Arthur et al 2013;Tetz et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing non-penetrating with penetrating glaucoma surgeries have reported that although canaloplasty may not be as effective as filtering surgery in lowering IOP without medication, complication rate and risk of serious vision-threatening adverse events are low (Ayyala et al 2011;Brusini & Tosoni 2012;Bruggemann et al 2013;Matlach et al 2013). In addition, the combination of canaloplasty with cataract surgery provides a better IOP reduction than single canaloplasty (Lewis et al 2007(Lewis et al , 2011Shingleton et al 2008;Bull et al 2011;Arthur et al 2013;Tetz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the suture ends are tied outside SC in order to increase SC inner wall/JCT deformation and thereby increase trabecular (conventional) outflow facility. 20,21 Various studies have shown that canaloplasty surgery reduces IOP more than does viscocanalostomy. 22 As a nonpenetrating glaucoma surgery, canaloplasty, like viscocanalostomy, has fewer surgical risks compared to trabeculectomy.…”
Section: Viscocanalostomy and Canaloplastymentioning
confidence: 99%
“…Surgical approaches to augment suprachoroidal outflow have also been explored with cyclodialysis, suprachoroidal implants, seton devices, and most recently, an ab externo gold shunt placed in the suprachoroidal space. (Pinnas and Boniuk, 1969;Krejci, 1972;Ozdamar et al, 2003;Jordan et al, 2006) Type Glaucoma surgery This chapter, addresses the available knowledge for the novel drainage devices; devices which attempt to assist with flow regulation such as the Ex-PRESS mini-glaucoma shunt (Alcon Laboratories, Inc., Fort Worth, TX) ), Schlemm's canal surgical procedures, including nonpenetrating canaloplasty surgery ( Lewis et al, 2007), the Glaukos trabecular micro-bypass iStent (Nichamin, 2009) the Trabectome microelectrocautery device (Nguyen, 2008) and the suprachoroidal outflow gold microshunt device (GMS) (Melamed et al, 2009) (Table 1).Published data is limited as many of these devices are currently in investigation and undergoing clinical trials.…”
Section: Drainage Devicesmentioning
confidence: 99%